Changes in Driving Performance Following Shoulder Arthroplasty. (7th September 2016) - Hasan, Saqib; McGee, Alan; Garofolo, Garret; Hamula, Mathew; Oh, Cheongeun; Kwon, Young; Zuckerman, Joseph
Abstract : Background: With this study, we sought to quantify perioperative changes in driving performance among patients who underwent anatomic or reverse shoulder arthroplasty. Methods: Using a driving simulator, 30 patients (20 anatomic and 10 reverse total shoulder arthroplasties) were tested preoperatively and at 2 weeks (PO2), 6 weeks (PO6), and 12 weeks (PO12) postoperatively. The total number of collisions, centerline crossings, and off-road excursions (when the vehicle traversed the lateral road edge), and scores on a visual analog scale (VAS) for pain and the Shoulder Pain and Disability Index (SPADI) were recorded at each driving trial. Results: The mean number of collisions increased from 5.9 preoperatively to 7.4 at PO2 and subsequently decreased to 5.6 at PO6 and 4.0 at PO12 (p = 0.0149). In addition, the number of centerline crossings decreased from 21.4 preoperatively to 16.3 at PO12 (p < 0.05). Multivariate analysis of the data demonstrated that increased VAS for pain scores, older age, and less driving experience had a negative impact on driving performance. Conclusions: Driving performance returned to preoperative levels at 6 weeks after shoulder arthroplasty. By 12 weeks postoperatively, patients demonstrated improved driving performance compared with preoperative performance. On the basis of our findings, clinicians can suggest a window of 6 to 12 weeks postoperatively for the gradual return to driving. However, for patients of older age, with less driving experience, or with greater pain, a return to driving at closer to 12 weeks postoperatively should be recommended. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.